2015
DOI: 10.1111/ecc.12410
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive functions and health-related quality of life in glioblastoma patients: a concise review of the literature

Abstract: The maintenance of quality of life in patients with high-grade glioma is an important endpoint during treatment, particularly in those with glioblastoma multiforme, given its dismal prognosis; thus, the primary aims of treatments are to reduce morbidity, restore or preserve neurological functions, and the capacity to perform daily activities. This review aims to summarise what is currently known about neurocognitive outcome and quality of life in patients with high-grade glioma, particularly in glioblastoma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 95 publications
1
32
0
2
Order By: Relevance
“…5 People living with brain tumors have numerous neurological impairments related to their tumors and cancer treatment. [6][7][8] Mukand et al found that 74.5% of patients admitted to an inpatient rehabilitation facility (IRF) for brain tumor rehabilitation had three or more neurologic deficits and 39.2% had five or more deficits. 6 The most common neurologic deficits in this study included "impaired cognition (80%), weakness (78%), visual-perceptual deficit (53%), sensory loss (38%), and bowel-bladder dysfunction (37%)."…”
Section: Introductionmentioning
confidence: 99%
“…5 People living with brain tumors have numerous neurological impairments related to their tumors and cancer treatment. [6][7][8] Mukand et al found that 74.5% of patients admitted to an inpatient rehabilitation facility (IRF) for brain tumor rehabilitation had three or more neurologic deficits and 39.2% had five or more deficits. 6 The most common neurologic deficits in this study included "impaired cognition (80%), weakness (78%), visual-perceptual deficit (53%), sensory loss (38%), and bowel-bladder dysfunction (37%)."…”
Section: Introductionmentioning
confidence: 99%
“…Like functional decline, cognitive dysfunction is common and affects daily functioning, independence, and medical decision-making [ 26 ]. In addition to cognitive impairment caused by the tumor itself, some cancer-directed therapies (surgery and radiation) and symptomatic treatments (anti-epileptic drugs and corticosteroids) have been associated with worsening cognitive deficits [ 26 ]. In the last weeks of life, up to 50% of patients have lost their ability to make decisions for themselves, emphasizing the importance of early goals of care discussions [ 27 ].…”
Section: Approachmentioning
confidence: 99%
“…These symptoms restrict the ability to drive, work, and live independently, and reduce people's social role functioning and quality of life (QoL) (Cubis, Ownsworth, Pinkham, & Chambers, 2018). The stress associated with the diagnosis, an uncertain prognosis, and complex neurological and functional impairments has a major impact on the mental health and QoL of people with brain tumour and their family caregivers (Bergo et al, 2015;Ownsworth, Henderson, & Chambers, 2010).…”
Section: Introductionmentioning
confidence: 99%